Managerial Performance Analysis from a Financial Perspective as an Effort to Realize Sustainable BUMDes Governance - Siti Muntahanah; Heru Cahyo; Chusnul Maulidina Hidayat (International Journal Labs, 2025)
This study aims to analyze the influence of planning, accountability, and accounting information systems on the performance of Village-Owned Enterprises (BUMDes) in Banyumas Regency, as well as examine the role of internal control as a moderation variable. This study uses a quantitative approach with a survey method of 171 BUMDes spread across the Banyumas area. The data analysis technique was carried out using Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach. The results of the study show that planning, accountability, and accounting information systems have a positive and significant effect on the performance of BUMDes. In addition, internal control has been proven to moderate the relationship between the three independent variables on the performance of BUMDes, so that internal control can strengthen the positive influence of planning, accountability, and accounting information systems on the performance of BUMDes. The implications of this study show the importance of implementing a strong internal control system in supporting sustainable and accountable BUMDes governance.